Carbohydrate hydrolyzing enzyme inhibitor property, antioxidant and phytochemical analysis of Cassia auriculata, Delonix regia and Vinca rosea Linn: an in vitro study - Nilam Yadao, Charles Lekhya Priya, Kokati Venkata Bhaskara Rao (Journal of Applied Pharmaceutical Science, 2015)
The study comprises the evaluation of antidiabetic and antioxidant activities of Cassia auriculata, Delonix rega and Vinca rosea belonging to Fabaceae family. Initially, In vitro α-Glucosidase inhibitor activity was performed as a preliminary screening for petroleum ether, chloroform, ethyl acetate, methanol and aqueous extracts of three collected plants. In comparison with all the extracts, methanol extracts shown promising activity with IC50 values of 58.52μg/ml, 83.46μg/ml and 77.41μg/ml for C. auriculata, D. regia and V. rosea respectively. Hence, these three extracts were further selected for DPPH radical scavenging activity. C. auriculata resulted in 96% DPPH radical scavenging activity fallowed by D. regia (78%) and V. rosea (60%). Hence, methanol extract of C. auriculata was selected to evaluate α-amylase inhibitor potential, reducing power capacity and also quantified for total phenolic and total flavonoid content within them. Selected extract showed efficient α-amylase inhibitor activity, reducing power capacity and good amount of phenolics and flavonoids. HPTLC analysis identified five polyphenols and FT-IR analysis detected –OH functional groups in the extract. GC-MS analysis detected hydroquinone, myoionositol and bulletin. It can be concluded that these compounds within the methanol extract of C. auriculata might be accountable for antidiabetic and antioxidant nature of the plant. In future, bioactive compound could be isolated and used as a carbohydrate hydrolyzing enzyme inhibitor to treat type 2 diabetic individuals.
Keywords: Cassia auriculata, Delonix reiga, Vinca rosea, alpha glucosidase, alpha amylase, HPTLC, FT-IR, GC-MS.